ANALISIS WHISTLEBLOWING SYSTEM DIREKTORAT JENDERAL PAJAK UNTUK MENGOPTIMALKAN PENERIMAAN PAJAK (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA SURABAYA SAWAHAN) - ANISARI KHULSUM, UMY (Jurnal Akuntansi AKUNESA, 2014)
Abstract Many cases in DJP’s environment made DJP encouraged to create control strategies, which was whistleblowing system. Hopefully with this whistleblowing system, tax officials to be more careful and responsible for the public service, in order to increased public trust. One measure of success about DJP’s strategy was the achievement taxes acceptance. This study aims to determined the taxes acceptance before and after implementation of the whistleblowing system in KPP Pratama Surabaya Sawahan. Whistleblowing system was breach prevention and handling of reporting violations system in DJP's environment. This article used a descriptive analysis, which compares the average taxes acceptance before and after implementation ofthe whistleblowing system. The results showed tha tafter implementation of whistleblowing system, average revenues increased in KPP Pratama Surabaya Sawahan. This indicated that the whistleblowing systems contributed positively to the tax revenue in KPP Pratama Surabaya Sawahan. Keywords: whistleblowing system, public trust, taxes acceptance.